2011
DOI: 10.1136/ard.2010.128637
|View full text |Cite
|
Sign up to set email alerts
|

High disease activity is associated with an increased risk of infection in patients with rheumatoid arthritis

Abstract: In this large cohort of RA patients, higher disease activity was associated with a higher probability of developing infections.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
184
4
8

Year Published

2011
2011
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 292 publications
(229 citation statements)
references
References 25 publications
19
184
4
8
Order By: Relevance
“…We have two explanations for this discrepancy. First, in both arms of the Utrecht Study disease control was not tight, in contrast to in CAMERA-II; inflammatory disease has negative effects on bone, and also on lipids, endothelium, glucose metabolism and infection risk [17,18,19,20]. In this way, negative effects of the inflammatory disease are entangled with adverse effects of the GC therapy given for the inflammatory disease.…”
Section: Discussionmentioning
confidence: 99%
“…We have two explanations for this discrepancy. First, in both arms of the Utrecht Study disease control was not tight, in contrast to in CAMERA-II; inflammatory disease has negative effects on bone, and also on lipids, endothelium, glucose metabolism and infection risk [17,18,19,20]. In this way, negative effects of the inflammatory disease are entangled with adverse effects of the GC therapy given for the inflammatory disease.…”
Section: Discussionmentioning
confidence: 99%
“…10 Au et al reported that increased risk of infections is related to RA disease activity, independent of treatment with DMARDs, with more active disease associated with higher rate of all types of infections. 29 Also, the presence of airways colonization in patients with RA-BR was reported to be associated with increased risk of infections (2.5 Ϯ 1.7 infections per patient-year). 30 However, in the same study, the use of DMARDs was a more powerful predictor of lowerrespiratory-tract infection than airway colonization, consistent with other reports.…”
Section: Infectionsmentioning
confidence: 99%
“…In this RA population, risk of PJI was only 3.5% if revision arthroplasty surgery was performed in a joint with no prior PJI [5]. Active RA is also a risk factor for infection, and patents with more swollen and tender joints are at higher risk for infection, adding to the conflict between holding and continuing disease-modifying anti-rheumatoid drugs (DMARDs) perioperatively [1].…”
Section: Introductionmentioning
confidence: 99%